Effect of essential and vegetable oil blend supplementation on animal performance, feed intake, rumen fermentation and rumen microbial populations of crossbred steers finished in a pasture system (Research, Society and Development, 2020)
Recent years have seen a general increase in consumer concern regarding the profile of additives in animal feed and food sources, prompting the industry to study essential oil blends that have been promoted to replace synthetic products. This study evaluated the effect of essential oil blends supplementation on animal performance, feed intake, rumen fermentation and rumen microbial populations in crossbred steers finished in a pasture system. A total of 40 steers (½ Bons Mara vs. ½ Nellore) with a mean age of 20 ± 2.0 months and a mean body weight of 416.9 ± 5.56 kg were distributed in a completely randomized design with five diets and eight replications per diet. The five experimental diets were: CONT – basal diet, and oil blend inclusion in dosages of 1500, 3000, 4500 or 6000 mg/animal/d. Animal performance was similar among diets. The forage intake, crude protein, neutral detergent fiber, ethereal extract, non-fibrous carbohydrates, and the digestibility of crude protein, neutral detergent fiber, and non-fibrous carbohydrates were greater when essential oil blends were fed to steers. There was an increase in the concentrations of rumen ammonia nitrogen, and propionic and isovaleric volatile fatty acids when essential oil blends were used. The microbiological population of the rumen was similar among the five diets. Our results suggest that the inclusion of doses above 1500 mg/animal/ is high for livestock grazing on temperate pasture, further studies are needed to identify a promising dose to replace antimicrobial additives.